2015
DOI: 10.1016/j.jweia.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stable atmospheric boundary layers on wind-turbine wakes within offshore wind farms

Abstract: a b s t r a c tIn terms of predicting wind turbine wakes, the stably stratified atmospheric boundary layer (SABL) is taking an exceptional position as wake effects and thus loads on subsequent turbines are stronger. In this study we show the impact of the SABL on power production and wake effects (power deficits) in offshore wind farms by means of measurements as well as large-eddy simulations (LES). Measurements show enhanced wake effects in the SABL compared to the unstable situation. Another influence on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 28 publications
3
90
0
Order By: Relevance
“…In the current case, the maximal directional change is approximately 2 • near the end of the farm. Dörenkämper et al (2015) also observed a slight deviation to the left for a wind farm under stable atmospheric conditions, and attributed this deflection to the decrease in Coriolis force. Other studies reported wind farm wakes turning away from the pressure gradient towards the geostrophic wind direction (Van der Laan et al 2015; Volker et al 2015), and they attributed this effect to turbulent transport of momentum from above.…”
Section: Allaerts and J Meyersmentioning
confidence: 89%
“…In the current case, the maximal directional change is approximately 2 • near the end of the farm. Dörenkämper et al (2015) also observed a slight deviation to the left for a wind farm under stable atmospheric conditions, and attributed this deflection to the decrease in Coriolis force. Other studies reported wind farm wakes turning away from the pressure gradient towards the geostrophic wind direction (Van der Laan et al 2015; Volker et al 2015), and they attributed this effect to turbulent transport of momentum from above.…”
Section: Allaerts and J Meyersmentioning
confidence: 89%
“…More recently, Churchfield et al (2016) and Abkar and Porté-Agel (2016) have shown similar results using LES of wakes in a stable ABL. By contrast, Dörenkämper et al (2015) reported a small anticlockwise deflection in a LES of a wind farm wake in a stable ABL. Dörenkämper et al (2015) generated the ABL with a precursor simulation using a different roughness length compared to the one applied in the wind farm simulation in order to model coast effects on an offshore wind farm.…”
Section: Introductionmentioning
confidence: 85%
“…Thus, the axial and tangential velocity at the rotor disk U n and U t are selected as the unknown parameters instead of a and a [31][32][33]. In this study, a coupled approach is adopted for the ADM-R Energies 2018, 11, 665 6 of 24 model in the yawed condition, in which U n and U t are directly obtained from the CFD simulation result of local velocities on the rotor disk U x , U y , U z by using the following transformation:…”
Section: = Cosmentioning
confidence: 99%